The Use of Picture Storybooks on Literacy in Early Childhood - Mardiana, Mardiana; Upu, Hamzah; Syamsuardi, Syamsuardi; Wahira, Wahira; Herlina, Herlina (PT. Riset Press International, 2026)
Picture storybooks not only attract children's attention with colorful illustrations, but can also improve language skills, especially in terms of literacy. By listening to stories and looking at pictures, children can recognize new words, understand the context in which they are used, and enrich their understanding of the world around them. This study aims to find out the description of the use of picture storybooks in early childhood, find out the description of literacy skills, and find out the influence of the use of picture storybooks on early childhood literacy skills. This study uses a quantitative approach to determine the effect of the use of picture storybooks on literacy in early childhood. The research design used is Pre Experimental in the form of One Group Pretest-Posstest Design. The data analysis technique used in this study is descriptive statistical analysis, Inferential Statistical Test (Wicoxon Signed rank test). The results of the study showed that the results of the N-Gain analysis, the literacy ability of early childhood after using picture storybooks increased in the medium category, showing moderate development and only 2 children were in the low category. These findings suggest that the use of picture storybooks is effective in improving literacy skills, although the increase has not yet reached the high category. Thus, it can be concluded that the use of picture storybooks has a positive and significant effect on improving early childhood literacy skills. The research is expected to be a reference and open up new study space related to the use of learning media in improving children's abilities. Findings on improving abilities obtained after treatment show that the selection and modification of appropriate learning media has the potential to have a positive impact on children's development.